A synergistic effect between gluconate and molybdate on corrosion inhibition of recirculating cooling water systems. (1st April 2018) - Ou, Hsin-Hung; Tran, Quynh Thi Phuong; Lin, Po-Hsun
Graphical abstract: Highlights : A new corrosion inhibitor (NCI) consisting of gluconate along with a relatively low amount of molybdate and nitrite was developed. The corrosion of C-steel in the presence of gluconate and molybdate is thermodynamically and kinetically unfavorable. Gluconate could bridge the molybdate and iron, resulting in the formation of the protective film that prevents the corrosion of C-steel. The pilot test showed no increase in microbial growth in the presence of gluconate with a complementary biocide program. Abstract: A new corrosion inhibitor (NCI) consisting of gluconate along with a relatively low amount of molybdate and nitrite was developed. A synergistic effect between molybdate and gluconate on the corrosion inhibition of C-steel was investigated. The polarization measurement indicates that the corrosion of C-steel in the presence of gluconate is thermodynamically and kinetically unfavorable as compared to that with molybdate alone. According to FIB-SEM, FTIR, and XPS experiments, an inhibition mechanism is proposed whereby the gluconate could bridge the molybdate and iron, which is responsible for the formation of the protective film against the corrosion of C-steel.